3D Coaxial Printing Tough and Elastic Hydrogels for Tissue Engineering Using a Catechol Functionalized Ink System. Issue 24 (25th October 2020) - Zhou, Ying; Yue, Zhilian; Chen, Zhi; Wallace, Gordon
Abstract: 3D printing is now popular in tissue engineering as it provides a facile route to the fabrication of scaffolds with/without living cells with a predesigned geometry. The properties of the ink constituents are critical for printing structures to meet both mechanical and biological requirements. Despite recent advances in ink development, it remains a challenge to print biopolymer based tough and elastic hydrogels. These hydrogels are in great demand as they can mimic the biomechanics of soft tissues such as skin, muscle, and cartilage. In this study, a catechol functionalized ink system is developed for 3D coaxial printing tough and elastic hydrogels. The ink is based on biopolymers including catechol modified hyaluronic acid (HACA) and alginate. A novel crosslinking strategy is proposed, involving simple ionic crosslinking, catechol mediated crosslinking, and Michael addition that are all induced under mild conditions. The HACA and alginate form a double network with high fracture toughness and elasticity, while proteins such as gelatin can be integrated with the HACA/alginate hydrogel during printing to improve cell interactions. The printed constructs demonstrate high cytocompatibility and support the differentiation of myoblasts into aligned myotubes. The catechol functionalized ink can be further modified to target various applications in soft tissue engineering. Abstract : A catechol functionalized ink system based on hyaluronic acid and alginate is developed for coaxial printing tough and elastic hydrogel. The printing process involves simple ionic crosslinking and catechol chemistry, during which bioactive proteins such as gelatin can be easily immobilized on the hydrogel. The printed hydrogels demonstrate high compatibility with mouse myoblasts.